2008
DOI: 10.1002/j.1556-6978.2008.tb00046.x
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Collaborative Teaching Teams in Counselor Education

Abstract: Teaching's importance has increased for faculty members and is reflected in the selection criteria for new faculty, particularly those in counselor education. Thus, graduate programs need to provide students with opportunities to obtain teaching experience and enhance their pedagogical training. The collaborative teaching teams model is intended to assist counselor educators in preparing doctoral‐level counseling students for careers in academia. Recommendations for model implementation are provided and specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
47
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(59 citation statements)
references
References 19 publications
12
47
0
Order By: Relevance
“…feedback about teaching, reflecting on that feedback, and having discussions with faculty and other students about teaching issues were highlighted in the responses to this survey. Findings suggested a need to create structured approaches for teacher training, and are consistent with the description of a teaching collaborative model presented by Orr et al (2008). Orr et al"s model of a teaching collaborative, which involves the concepts mentioned above could be beneficial in training doctoral students to teach; and this teaching collaborative is very similar to the regimented way in which counselor education programs train students to be counselors.…”
supporting
confidence: 76%
“…feedback about teaching, reflecting on that feedback, and having discussions with faculty and other students about teaching issues were highlighted in the responses to this survey. Findings suggested a need to create structured approaches for teacher training, and are consistent with the description of a teaching collaborative model presented by Orr et al (2008). Orr et al"s model of a teaching collaborative, which involves the concepts mentioned above could be beneficial in training doctoral students to teach; and this teaching collaborative is very similar to the regimented way in which counselor education programs train students to be counselors.…”
supporting
confidence: 76%
“…For example, being a participant in a teaching practicum was given a mean rating of 5.56, which indicates that this was rated as highly effective. That rating also provides support for more experiential training of teachers, and is consistent with Orr et al (2008) who observed that after participating in a supervised teaching practicum, students reported having greater depth of knowledge about the counseling curriculum, understanding how to develop a course and implement it from start to finish, and developing a greater awareness of the role of a teacher in the counseling classroom. Sharing of resources with faculty had a mean effectiveness rating of 4.06, teaching under supervision had a mean rating of 5.60 (also suggested by Austin, 2002a;2002b and Orr et al), having discussions with faculty about teaching philosophy had a mean rating of 4.76, and having discussions with faculty about why instructional decisions are made in courses had a mean rating of 4.81.…”
Section: Resultssupporting
confidence: 65%
“…Many responses indicated the desire to be mentored into the role of teacher by experienced faculty. This information supports the ideas of Anderson and Shannon (1988) who wrote that the purpose of a mentor is to integrate a new person into a professional role that is already held by the mentor and Orr et al (2008) who suggest that faculty supervisors of students in teaching take a mentoring role in helping doctoral students transition from learner to leader in the classroom. Examples of responses were "more mentoring into the role of faculty member", "better mentoring" and "Mentorship by faculty in the areas of teaching, research and service...to learn about the different types involved and the expectations for tenure".…”
Section: Responses To Open Ended Survey Item About Teaching Preparationsupporting
confidence: 58%
See 2 more Smart Citations